2017
DOI: 10.14744/phd.2017.03016
|View full text |Cite
|
Sign up to set email alerts
|

Perception of working environment, psychological distress and affecting factors in nurses working intensive care units

Abstract: The purpose of this study is to analyze intensive care nurses' perceptions of work environment, psychological distress and the factors that affect them. Methods: This is a descriptive study. Its sample included 320 nurses working in the adult patient intensive care units of six hospitals (three university and three state hospitals) in the provincial center of Ankara. Data were collected using the Nurse Introductory Information Form, the Work Environment Scale and the General Health Questionnaire-12. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The findings of this study indicated that, among the ICU nurses, 25.6% experienced moderate or high levels of depression, while 46.3% experienced moderate or severe anxiety. Data obtained from similar studies reported that nurses’ prevalence of anxiety was between 10.2% and 32%, while their depressive symptoms were between 11% and 31% (Altınöz & Demir, 2017; de Boer et al, 2014; Karanikola et al, 2015). The findings showed that the depression rates of the ICU nurses were similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study indicated that, among the ICU nurses, 25.6% experienced moderate or high levels of depression, while 46.3% experienced moderate or severe anxiety. Data obtained from similar studies reported that nurses’ prevalence of anxiety was between 10.2% and 32%, while their depressive symptoms were between 11% and 31% (Altınöz & Demir, 2017; de Boer et al, 2014; Karanikola et al, 2015). The findings showed that the depression rates of the ICU nurses were similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%